Analysis of the market structures and systems for indigenous fruit trees: the case for Uapaca Kirkiana in Zambia - Moombe, Kaala Bweembelo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2005.